In-utero gastric perforation from combined duodenal and esophageal atresia without consistent polyhydramnios. Issue 12 (28th December 2021) - Lyttle, Bailey D; Liechty, Kenneth; Corkum, Kristine; Galan, Henry; Behrendt, Nicholas; Zaretsky, Michael; Bruny, Jennifer; Derderian, S Christopher
Abstract: We present a case in which prenatal imaging at 21-weeks' gestation suggested duodenal atresia with a double-bubble sign and enlarged stomach. Fetal magnetic resonance imaging findings demonstrated dilation of the stomach and proximal duodenum favoring duodenal atresia but no indications of esophageal atresia. Subsequent prenatal imaging demonstrated interval spontaneous decompression of the stomach without the development of polyhydramnios, obscuring the diagnosis. Postnatally, initial abdominal radiography showed a gasless abdomen, and an oral gastric tube could not pass the mid-esophagus, raising concern for pure esophageal atresia. Intraoperative findings were consistent with duodenal atresia, pure esophageal atresia and a gastric perforation due to a closed obstruction. In this case report, we review the prenatal diagnostic challenges and the limited literature pertaining to this unique pathology.